ITGB6 inhibits the proliferation of porcine skeletal muscle satellite cells. (30th September 2021) - Qiao, Jiaxin; Wang, Shanshan; Zhou, Jian; Tan, Baohua; Li, Zicong; Zheng, Enqin; Cai, Gengyuan; Wu, Zhenfang; Hong, Linjun; Gu, Ting
Abstract: The formation of embryonic muscle fibers determines the amount of postnatal muscles and is regulated by a variety of signaling pathways and transcription factors. Previously, by using chromatin immunoprecipitation‐sequencing and RNA‐Seq techniques, we identified a large number of genes that are regulated by H3K27me3 in porcine embryonic skeletal muscles. Among these genes, we found that ITGB6 is regulated by H3K27me3. However, its function in muscle development is unknown. In this study, we first verified that ITGB6 was differentially regulated by H3K27me3 and that its expression levels were upregulated in porcine skeletal muscles at embryonic Days 33, 65, and 90. Then, we performed gain‐ or loss‐of‐function studies on porcine skeletal muscle satellite cells to study the role of ITGB6 in porcine skeletal muscle development. The proliferation of porcine skeletal muscle satellite cells was studied through real‐time polymerase chain reaction, Cell Counting Kit‐8, 5‐ethynyl‐2′‐deoxyuridine staining, Western blot, and flow cytometry analyses. We found that the ITGB6 gene was regulated by H3K27me3 during muscle development and had an inhibitory effect on the proliferation of porcine skeletal muscle satellite cells.